Self-compassion in individuals with substance use disorder: the association with personal growth and well-being. Issue 3 (8th June 2022) - Shreffler, Jacob; Thomas, J. Jeremy; McGee, Suzanne; Ferguson, Brian; Kelley, Justin; Cales, Rick; Cales, Shannon; Huecker, Martin
Abstract: Individuals with Substance Use Disorder (SUD) who do not have empathy toward oneself, or self-compassion, may limit their opportunities for personal growth and overall well-being. Due to scarce empirical studies examining interactions between self-compassion, personal growth and well-being in persons with SUD, the goal of this research was to examine associations among these concepts. A survey was administered to patients in treatment for SUD using validated scales (Sussex-Oxford Compassion for the Self Scale (SSOCS-S), Personal Growth Initiative (PGI) Scale-II, and World Health Organization (WHO)-5 Well-Being Index) and 153 responses were collected. Over two-thirds (69.9%) of the sample were seeking treatment for addiction to prescription opioids; other substances used included heroin (37.3%), methamphetamine (30.7%), benzodiazepines (17%), fentanyl (15.7%), cocaine (9.8%), alcohol (9.8%), and other substances (3.9%). Gender identity, age, and length of treatment did not correlate with personal growth or well-being. Total self-compassion was significantly associated with personal growth initiative ( r = .568, p  < 0.001) and each of PGI subscales. Additionally, total self-compassion was significantly associated with well-being ( r = .567, p  < 0.001). When interacting with persons with SUD, we should instill the practice of self-compassion which may help accomplish personal growth and enhance well-being. These individuals need support and humanity from not only providers and loved ones, but also themselves.